Pelatihan Penggunaan Software Geogebra Dalam Pembelajaran Matematika Pada Materi SPLDV Di MTs. Swasta Al-Jihad Medan - Muhammad Rizky Mazaly; Doni Irawan Saragih; Riska Amalia (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
Community service activities (PKM) are conducted in the form of training activities for the use of geogebra software for students in solving the problems of the system of Linear Equations of two variables (SPLDV) in MTs. Private Al-Jihad Battlefield. The number of participants / students in this service activity amounted to 16 MTs students. Private Al-Jihad Battlefield. The purpose of this service activities include 1) to know how to use geogebra software in mathematics learning on SPLDV material; and 2) knowing the student's response to how to use geogebra software in mathematics learning on SPLDV material. The method implemented in this service activity consists of four stages. Evaluation of service activities is carried out through a questionnaire/questionnaire given to the students after the service activities carried out. Data analysis is done quantitatively descriptive. The first stage is the stage of observation of the students. The second stage is the stage of providing training materials on the use of geogebra software. The third stage is the stage of giving problems or SPLDV questions that will be solved by students in groups. The fourth stage is the stage of evaluating activities. The conclusions obtained in this service activity are 1) the students already know how to use geogebra software in solving SPLDV problems; and 2) the response of students in this activity is categorized as good. Thus, it is expected that the school management can facilitate students in implementing computer applications in mathematics learning.